Too complex to digest? Federal tax bills and their processing in US financial markets - Hamza Bennani; Matthias Neuenkirch (International Tax and Public Finance, 2023)
In this paper, we analyze whether the textual complexity of tax bills affects financial markets. Based on the Flesch-Kincaid grade level of the 32 tax bills identified by Romer (Am Econ Rev 100(3):763–801, 2010)in the period 1962–2003, we assess the relationship between tax bills' textual complexity and financial markets in various windows around the signing of a bill. Our results show a negative (positive) and significant relationship between the present value of tax bills and changes in the 10-year government bond yields (S &P 500 returns). The magnitude of this relationship increases over time, suggesting that market participants underreact at first and need a couple of days to digest the information contained in the tax bills. This delay can be explained by the textual characteristics of the bills in the case of the 10-year yields as a lower readability partly counteracts the negative relationship for up to three days after the signing of a tax bill. In the case of the stock market, we find similar evidence, but only for a part of the readability measures employed in this paper.
Keywords: G14; H20; H30; 340; Complexity; Financial markets; Readability; Tax bills